Strategi Kreatif Iklan Parfum KENZO World Versi The New Fragrance - Annisa Nurseptianditha; Denny Antyo Hartanto; Romdhi Fatkhur Rozi (Program Studi Film dan Televisi Universitas Jember, 2019)
This research discusses creative strategy the of KENZO World The New Fragrance version ad. Purpose of the research is to find out the creative ideas and the impact to the audiece. Research data based on repeated observation and describe with additional theory of Mise-en-scene. This research uses qualitative methods with observation, interview and literature study, that expected to show the effectiveness of crative strategy.